2016
DOI: 10.5897/ajar2015.10759
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different irrigation levels with different qualities of water and organic substrates on cultivation of pepper

Abstract: The amount of water needed to meet the water requirement of crops and use of alternative organic substrates affect the development of the plants' nutrients. The objective of this research is to evaluate the cultivation of pepper (Capsicum chinense) under different organic substrates and irrigation levels with supply water and wastewater. The experiment was conducted in a greenhouse at Campina Grande, Paraíba, Brazil. Biquinho BRS Moema pepper species was used. The experimental design was randomized block in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…This was in agreement with previous studies on cucumber and tomato crops when irrigating with FW and TWW [34,82]. In another study on the effect of different irrigation levels with different qualities of water on the cultivation of pepper [83], it was reported that TWW provided nutrients for the plants and determined an increase in plant growth.…”
Section: Effects Of Source Of Irrigation Water and Type Of Plant Habit On Ornamental Pepper Plantssupporting
confidence: 92%
“…This was in agreement with previous studies on cucumber and tomato crops when irrigating with FW and TWW [34,82]. In another study on the effect of different irrigation levels with different qualities of water on the cultivation of pepper [83], it was reported that TWW provided nutrients for the plants and determined an increase in plant growth.…”
Section: Effects Of Source Of Irrigation Water and Type Of Plant Habit On Ornamental Pepper Plantssupporting
confidence: 92%
“…Sendo assim, tem-se os valores de 9,39 e 7,94 para os substratos 1 e 2 respectivamente. Silva et al (2016), ao estudar pimenta biquinho em diferentes lâminas de irrigação (20,40,60, 80 e 100% da evapotranspiração da cultura) notaram que a lâmina de 100% demonstrou o maior diâmetro de caule (7mm), já neste estudo o valor médio chegou a 12,46 mm na fase 2, resultando em valores superior ao obtidos pelo pesquisado.…”
Section: Parâmetrosunclassified